MHD darcy-forchheimer flow of SWCNT-H2O nanofluid over a porous stretching sheet - Suresh Kumar; Sushila Choudhary; Kiran Kumari; Anil Sharma; Prasun Choudhary (International Journal of Thermofluids)
Single walled carbon nanotubes exhibit unique electronic properties that make them ideal for miniaturizing electronics and serving as excellent conductors in various nanotechnological applications. The aim of this numerical simulation of water-based single-walled carbon nanotube (SWCNT) nanofluid flow over a vertical porous sheet is to study the flow and heat transfer characteristics of this nanofluid through a non-darcy permeable medium. Other flow controlling conditions, like viscous dissipation and a uniform magnetic field, are also included during this study. The current analysis is an innovative in terms of stagnation point flow for the described fluid system in the presence of Darcy-Forchheimer effect, Joule heating, and non-uniform heat generation/absorption impact. A mathematical framework is established using partial differential equations to depict the flow and temperature processes, using appropriate boundary conditions. We transformed the mathematical framework into dimensionless form using similarity parameters and subsequently solved it with Bvp4c MATLAB code. Numerical outcomes are presented via graphs and tables. When the velocity ratio parameter exceeds 1, the velocity profile decreases with increasing magnetic parameter due to the enhanced Lorentz force that opposes the fluid motion. Both fluid velocity and temperature profiles increase with rising mixed convection parameter and nanotube volume fraction due to enhanced buoyancy and convective effects.